Contribution of the voluntary sector to mental health crisis care in England: protocol for a multimethod study. Issue 11 (8th November 2017) - Newbigging, Karen; Mohan, John; Rees, James; Harlock, Jenny; Davis, Alex
Abstract : Introduction: Timely access to the right kind of support for people experiencing a mental health crisis can be problematic. The voluntary sector (VS) plays a key role in providing support and enabling access, but there is a knowledge gap concerning its contribution and interface with public services in mental health crisis care. This study aims to address this. Methods and analysis: The study has three empirical elements: (1) a national survey of voluntary sector organisations (VSOs) in England and national stakeholder interviews to develop a typology of organisations and interventions provided by VSOs; (2) detailed mapping of VS services in two regions through interviews and extending the national survey; (3) four case studies, identified from the regional mapping, of VS mental health crisis services and their interface with National Health Service (NHS) and local authority services, at both a system and individual level. Data collection will involve interviews with commissioners; VSO and NHS or local authority providers; and focus groups with people who have experience of VSO crisis support, both service users and carers; and mapping the crisis trajectory of 10 service users in each study site through narrative interviews with service users and informal carers to understand the experience of VSO crisis care and its impact. Ethics and dissemination: The University of Birmingham Humanities and Social Sciences Ethical Review Committee granted ethical approval (reference ERN_16–1183) for the national and regional elements of the study. Ethical review by the Health Research Authority will be required for the case study research once the sites have been identified from the first two elements of the study. A range of methods including a policy seminar, publication in academic journals and a tool kit for commissioners and practitioners will be produced to maximise the impact of the findings on policy and practice.